Ensino remoto emergencial: a percepção docente acerca das dificuldades enfrentadas durante a pandemia - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present study aimed to identify difficulties faced by professors of the higher course of Technology in Public Management regarding remote teaching activities during the Covid-19 pandemic. The research methodology was a case study, with a qualitative approach and descriptive character; Data collection was carried out through questionnaires prepared in Google Forms and sent via institutional e-mail to the participants and later interpreted through a content analysis. The theoretical framework is presented in two parts, the first of which deals with the ERE and its specificities and the second with the training of teachers and the tools to support the ERE. As for the results obtained, the reports of teachers who needed to acquire equipment and make home adaptations to adapt their working conditions stand out, as well as the difficulty in capturing the attention and participation of students, often transforming the class into a digital monologue.
Emergency remote teaching: teachers' perception of the difficulties faced during the pandemic
Keywords: Ensino remoto; Distanciamento social; Docência; Remote teaching; Social distancing; Teaching; CNPQ::CIENCIAS SOCIAIS APLICADAS